Lesion-based indicators predict long-term outcomes of pheochromocytoma and paraganglioma– SIZEPASS - Hanschell, Helena; Diaz-Cano, Salvador; Blanes, Alfredo; Talat, Nadia; Galatá, Gabriele; Aylwin, Simon; Schulte, Klaus Martin (Frontiers in Endocrinology, 2023)
Aim: We seek a simple and reliable tool to predict malignant behavior of pheochromocytoma and paraganglioma (PPGL).Methods: This single-center prospective cohort study assessed size of primary PPGLs on preoperative cross-sectional imaging and prospectively scored specimens using the Pheochromocytoma of the Adrenal Gland Scaled Score (PASS). Multiplication of PASS points with maximum lesion diameter (in mm) yielded the SIZEPASS criterion.Local recurrence, metastasis or death from disease were surrogates defining malignancy.Results: 76 consecutive PPGL patients, whereof 58 with pheochromocytoma and 51 female, were diagnosed at a mean age of 52.0±15.2 years. 11 lesions (14.5%) exhibited malignant features at a median follow-up (FU) of 49 months (range 4-172 mo). Median FU of the remaining cohort was 139 months (range 120-226 mo).SIZEPASS classified malignancy with an area under the curve (AUC) of 0.97 (95%CI 0.93-1.01; p<0.0001). Across PPGL, SIZEPASS >1000 outperformed all known predictors of malignancy, with sensitivity 91%, specificity 94%, and accuracy 93%, and an odds ratio of 72 fold (95%CI 9-571; P<0.001). It retained an accuracy >90% in cohorts defined by location (adrenal, extra-adrenal) or mutation status.The SIZEPASS>1000 criterion is a lesion-based, clinically available, simple and effective tool to predict malignant behavior of PPGLs independently of age, sex, location or mutation status.